Influenced factors in the delignification process of red meranti wood sawdust - Siti Noredyani, Abdul Rahman; Mimi Sakinah, Abdul Munaim (Universiti Malaysia Pahang, 2018)
Lignocellulosic biomass are plants that include forestry residue and agricultural residues that are mainly composed of cellulose, hemicelluloses and lignin. Red Meranti wood sawdust (RMWS) are one of lignocellulosic biomass that rich-cellulose content. To obtain cellulose, the pretreatments are needed to extract it from outer layer of lignin and hemicellulose by using the acid-chlorite delignification procedure aided with design of experimental from Design Expert 7.1 software. Four factors were selected in design of experiment using two level with half fraction factorial analysis were came out with total of 8 runs. The factors contributed were ratio acetic acid (AC) to RMWS (0.45 and 0.6), ratio sodium chlorite to RMWS (0.6 and 1.64), reaction time (4hr and 6hr) and temperature (55°C and 75°C). The results obtained were showed that the design model was substantial resulting with a coefficient of determination value of 0.9963. Two factors that generated the highest to the process were ratio SC to RMWS (B) and temperature (D). The percentage error between the actual and predicted value for lignin removal at 0.79% and 4.92%, which found to be less than 5%, and thus, the model was successfully validated.